Ibrutinib for improved chimeric antigen receptor T‐cell production for chronic lymphocytic leukemia patients. Issue 2 (28th July 2020) - Fan, Fuli; Yoo, Hyeon Joo; Stock, Sophia; Wang, Lei; Liu, Yibin; Schubert, Maria‐Luisa; Wang, Sanmei; Neuber, Brigitte; Hückelhoven‐Krauss, Angela; Gern, Ulrike; Schmitt, Anita; Müller‐Tidow, Carsten; et al.
Abstract: Chimeric antigen receptor T (CART) cells targeting CD19 have shown promising results in the treatment of chronic lymphocytic leukemia (CLL). However, efficacy seems to be inferior compared to diffuse large B‐cell lymphoma or acute lymphoblastic leukemia. Impaired T‐cell fitness of CLL patients may be involved in treatment failure. Less‐differentiated naïve‐like T cells play an important role in CART expansion and long‐term persistence in vivo. These cells are sparse in CLL patients. Therefore, optimization of CART cell production protocols enriching less differentiated T cell subsets may overcome treatment resistance. The B‐cell receptor inhibitor ibrutinib targeting Bruton's tyrosine kinase (BTK) is approved for the treatment of CLL. Besides BTK, ibrutinib additionally inhibits interleukin‐2‐inducible T‐cell kinase (ITK) which is involved in T‐cell differentiation. To evaluate the effect of ibrutinib on CART cell production, peripheral blood mononuclear cells from nine healthy donors and eight CLL patients were used to generate CART cells. T‐cell expansion and phenotype, expression of homing and exhaustion makers as well as functionality of CART cells were evaluated. CART cell generation in the presence of ibrutinib resulted in increased cell viability and expansion of CLL patient‐derived CART cells. Furthermore, ibrutinib enriched CART cells with less‐differentiated naïve‐like phenotype and decreased expression of exhaustion markers including PD‐1, TIM‐3 and LAG‐3. In addition, ibrutinib increased the cytokine release capacity of CLL patient‐derived CART cells. In summary, BTK/ITK inhibition with ibrutinib during CART cell culture can improve yield and function of CLL patient‐derived CART cell products. Abstract : What's new? Chimeric antigen receptor T (CART) cells targeting CD19 have shown promising results in chronic lymphocytic leukemia (CLL). However, naïve‐like T cells play an important role in CART expansion and long‐term persistence in vivo, and these cells are sparse in CLL patients. Here, the authors show that BTK/ITK inhibition with Ibrutinib during CART cell generation may improve CLL patient‐derived CART cell products and enhance CART cell function. Supplementing CART cell production with ibrutinib increases CART cell yields and enriches CART cells with less‐differentiated phenotypes and lower expression of exhaustion markers, representing a potential avenue to improve the clinical outcome of patients.